Understanding the impact of second-hand smoke exposure on clinical outcomes in participants with COPD in the SPIROMICS cohort. Issue 5 (9th March 2016) - Putcha, Nirupama; Barr, R Graham; Han, Meilan K; Woodruff, Prescott G; Bleecker, Eugene R; Kanner, Richard E; Martinez, Fernando J; Smith, Benjamin M; Tashkin, Donald P; Bowler, Russell P; Eisner, Mark D; Rennard, Stephen I; et al.
Abstract : Background: Second-hand smoke (SHS) exposure has been linked to the development of and morbidity from lung disease. We sought to advance understanding of the impact of SHS on health-related outcomes in individuals with COPD. Methods: Among the participants with COPD in SPIROMICS, recent SHS exposure was quantified as (1) hours of reported exposure in the past week or (2) reported living with a smoker. We performed adjusted regression for SHS with outcomes, testing for interactions with gender, race, smoking and obesity. Results: Of the 1580 participants with COPD, 20% reported living with a smoker and 27% reported exposure in the past week. Living with a smoker was associated with worse St George's Respiratory Questionnaire score (SGRQ, β 3.10; 95% CI 0.99 to 5.21), COPD Assessment Test score (β 1.43; 95% CI 0.52 to 2.35) and increased risk for severe exacerbations (OR 1.51, 95% CI 1.04 to 2.17). SHS exposure in the past week was associated with worse SGRQ (β 2.52; 95% CI 0.47 to 4.58), nocturnal symptoms (OR 1.58; 95% CI 1.19 to 2.10), wheezing (OR 1.34; 95% CI 1.02 to 1.77), chronic productive cough (OR 1.77; 95% CI 1.33 to 2.35) and difficulty with cough and sputum (Ease of Cough and Sputum scale, β 0.84; 95% CI 0.42 to 1.25). SHS was associated with increased airway wall thickness on CT but not emphysema. Active smokers, obese individuals and individuals with less severe airflow obstruction also had higher susceptibility to SHS for some outcomes. Conclusion: Individuals with COPD, including active smokers, have significant SHS exposure, associated with worse outcomes and airway wall thickness. Active smokers and obese individuals may have worse outcomes associated with SHS. Trial registration number: NCT01969344 (clinicaltrials.gov).